2012
DOI: 10.1245/s10434-012-2630-x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Radical Hysterectomy after Preoperative Brachytherapy for Stage IB1 Cervical Cancer: Feasibility, Results, and Surgical Implications in a Large Bicentric Study of 162 Consecutive Cases

Abstract: Radical hysterectomy using a laparoscopic approach is feasible and reproducible after initial BT for stage IB1 cervical cancer and is associated with excellent survival. Morbidity is close to that reported in patients treated with up-front surgery. In this large series, the morbidity associated with parametrial dissection and the fact that parametrial spread was observed in only 0.6% of the patients suggest that a simple extrafascial hysterectomy is perhaps sufficient in this context; the rate of urinary tract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 35 publications
4
18
0
Order By: Relevance
“…It is believed that preoperative radiotherapy or chemoradiotherapy can reduce the incidence of the mid-risk factors of cervical cancer after radical hysterectomy. This result is also consistent with the findings of C. Uzan et al [17].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…It is believed that preoperative radiotherapy or chemoradiotherapy can reduce the incidence of the mid-risk factors of cervical cancer after radical hysterectomy. This result is also consistent with the findings of C. Uzan et al [17].…”
Section: Discussionsupporting
confidence: 94%
“…Their results showed that postoperative pathological complete remission was significantly higher in the PR group than in the SD group (25.7% vs 11.4%), while there was no significant difference in local tumour control (LTC), distant metastasis-free survival (DMFS) or overall survival (OS) between the two arms. C. Uzan et al [17] analysed 162 patients who underwent laparoscopic radical hysterectomy after preoperative radiotherapy between 2003 and 2010. It was found that preoperative radiotherapy could reduce mid-risk factors, thus reducing postoperative radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies [4,5,9] also support the idea that with preoperative BT in some of the patients postoperative pelvic irradiation, responsible for most of the bladder and bowel complications, can be spared. In a series of 162 cases of stage IB1 cervical cancer treated with 60Gy preoperative uterovaginal BT followed by laparoscopic radical hysterectomy (LRH) [24], the need for postoperative adjuvant RChT was 7 %, compared to 24 % in the series reported by Pellegrino et al [25], including exclusively stage IB1 disease, or 66 % reported by Puntambekar et al [26], including stage IA2 and IB1 patients, who underwent LRH and pelvic LAD.…”
Section: Discussionmentioning
confidence: 96%
“…However, the National Comprehensive Cancer Network guidelines only recommend primary surgery followed by radiotherapy, depending on the prognostic factors detected in the surgical specimen 4. Nevertheless, image-guided brachytherapy is effective for delivering high radiation doses to cervical cancer tumors while limiting the dose delivered to organs at risk, and available retrospective data suggest that pre-operative brachytherapy is a safe and effective treatment 6–11. Therefore, this study aimed to describe the experience at our academic center, where early stage cervical cancer is treated using pre-operative brachytherapy followed by Wertheim-type hysterectomy, and to determine which patients might benefit from this strategy.…”
Section: Introductionmentioning
confidence: 99%